On a Matlab/Simulink of power quality issues in distribution system with the presence of electric arc furnaces and mitigation solution using active filter - Ngo, Van Thai; Bach, Quoc Khanh (JST: Engineering And Technology For Sustainable Development, 2022)
The randomly non-linearity of the conductance of the electric arc furnace produces voltage flicker and harmonics in power systems. Nowadays, the application of electric arc furnace in steel production industry in Vietnam also results in the said poor power quality and it’s been critical to find approperiate solutions for its mitigation recently. This paper develops a time-domain simulation of electric arc furnace that generates power quality issues such as voltage flicker and harmonics in distribution system and the solution using active filter for power quality mitigation in MATLAB/ SIMULINK and thus, it is possible to assess the influence of different parameters of electric arc furnace on the active filter sizing and calibration. The simulation results are also comparatively assessed with power quality data measured from the distribution system of the factory of Thien Phat Company.